Efficacy of guselkumab versus secukinumab in subpopulations of patients with moderate-to-severe plaque psoriasis: results from the ECLIPSE study. (19th May 2022) - Blauvelt, Andrew; Armstrong, April W.; Langley, Richard G.; Gebauer, Kurt; Thaçi, Diamant; Bagel, Jerry; Guenther, Lyn C.; Paul, Carle; Randazzo, Bruce; Flavin, Susan; Hsu, Ming-Chun; You, Yin; et al.
Abstract: Purpose: Guselkumab, an interleukin (IL)-23 inhibitor, effectively treats moderate-to-severe plaque psoriasis. Materials and methods: ECLIPSE, was a Phase 3, multicenter, 56-week, double-blinded, active-comparator study of guselkumab vs. secukinumab (IL-17A inhibitor) in patients with moderate-to-severe psoriasis. Patients were treated with guselkumab 100 mg ( n  = 534) or secukinumab 300 mg ( n  = 514) through week 44. Efficacy (at least a 90% and 100% improvement from baseline in Psoriasis Area and Severity Index [PASI 90 and PASI 100], Investigator's Global Assessment [IGA] 0/1, and IGA 0) was analyzed across subpopulations defined by baseline: age (<45, 45 to <65, and ≥65 years old), body weight, body mass index (BMI), psoriasis disease severity (body surface area, disease duration, PASI, and IGA), psoriasis by body regions (head, trunk, upper and lower extremities), and prior psoriasis medication history at week 48. Results: Overall, 1048 patients were randomized. At week 48, numerically greater proportions of patients achieved PASI 90, PASI 100, IGA 0/1, and IGA 0 with guselkumab vs. secukinumab regardless of baseline age, body weight, BMI, disease severity, body region, and prior medication. The largest differences were in patients ≥65 years old and patients weighing >100 kg. Conclusions: Guselkumab treatment provided greater efficacy vs. secukinumab at week 48 in most subpopulations of patients with psoriasis.